KEMISKINAN STRUKTURAL PADA PURNA PEKERJA MIGRAN PEREMPUAN : ANALISIS KEGAGALAN MOBILITAS EKONOMI PASCA MIGRASI BERULANG - Ramlafatma Ramlafatma (Nusantara Hasana Journal, 2026)
International labor migration is viewed as an effective strategy for improving household economic well-being. For low-income families, working as migrant workers offers an alternative to earn higher incomes compared to job opportunities in their home regions. Job opportunities are available for women, particularly in the Middle East and parts of Asia. However, observations on the ground indicate that the repeated migration experienced by many former migrant women does not always lead to sustainable economic mobility after working abroad. This study aims to analyze the structural poverty experienced by former female migrants and the factors contributing to the failure of economic mobility following repeated migration. The research employed a descriptive qualitative method. The findings indicate that the failure of post-migration economic mobility is influenced by the predominant use of remittances for household consumption, limited access to productive capital, gender inequality in asset ownership, weak economic reintegration programs, low financial literacy, and limited social capital to support business development. These conditions result in repeated migration becoming a survival strategy rather than a means of economic transformation. These findings show that the poverty experienced by former female migrants cannot be understood merely as individual failure, but rather as a consequence of social, economic, and institutional structures that limit their opportunities for economic mobility. Therefore, more comprehensive and gender-sensitive reintegration policies are needed to support the long-term well-being of former female migrants.